The Narrative Features in Love (Ghazal) Poetry Among the Poets of al-Tawa’if and Murabitin - HASAN MANSOOR MOHAMMED ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Love, or ghazal, is one of the most significant poetic genres in Arabic poetry, evoking emotional feelings that touch the depths of the heart and captivating the reader’s interest. Ghazal poets are committed to selecting appropriate and meaningful poetic images that reflect the passion and love in their souls and the souls of their audience. Their love experiences are conveyed through a diverse range of poetic images, including expressions of their sorrows and the pain of rejection or separation from their beloved, as well as the description of their happy days in the company of their loved ones. All of this is conveyed through a solidification of poetic images and ghazal poems, making them akin to a narrated story with relatable characters and events. The blending of narrative and poetry is a long-standing tradition, with the former being a big tent that covers most literary genres. The poet draws from the narrative to describe dialogue and story scenes, relying on a hierarchy in narrating events and portraying them. It’s important not to burden the ghazal poem with what it cannot bear, or demand that it contains all known narrative and storytelling techniques. Instead, we should appreciate the poem’s ability to benefit from and employ narrative techniques to serve its intended purpose, following the method adopted in its creation. The blending of poetry and narrative has a rich history, with Aristotle placing the epic within poetry and storytelling in Arabic poetry beginning with poets narrating their journeys and experiences while hunting for precious things and honey, as seen in the poems of Hatheel. As such, any cognitive vision that separates poetry and narrative requires a re-reading of its achievements and judgments